Using the locus of slack logic to determine whether the output form of inhibition of return affects an early or late stage of processing. (January 2020) - Klein, Raymond M.; Kavyani, Maryam; Farsi, Alireza; Lawrence, Michael A.
Abstract: Slower reaction times to targets presented at a previously cued or attended location are often attributed to inhibition of return (IOR). It has been suggested that IOR affects a process at the output end of processing continuum when it is generated while the oculomotor system is activated. Following the path set by Kavyani, Farsi, Abdoli, and Klein (2017) we used the locus of slack logic embedded in the psychological refractory period (PRP) paradigm to test this idea. We generated what we expected would be the output form of IOR by beginning each with participants making a target directed saccade which was followed by two tasks. Task 1, was a 2-choice auditory discrimination task and Task 2 was a 2-choice visual localization task. We varied the interval between the onsets of the two targets associated with these two tasks (using TTOAs of 200, 400, or 800 msec). As expected the visual task suffered from a robust PRP effect (substantially delayed RTs at the shorter TTOAs). There was also a robust IOR effect with RTs to localize visual targets being slower when the targets were presented at a previously fixated location. Importantly, and in striking to our previous results wherein we generated the input form of IOR, in the present study there was an additive effect between IOR and TTOA on RT2. As implied by the locus of slack logic, we therefore conclude that the form of IOR generated when the oculomotor system is activated affects a late stage of processing. Converging evidence for this conclusion, from a variety of neuroscientific methods, is presented and the dearth of such evidence about the input form of IOR is noted.